The sympathetic nervous system shapes the tumor microenvironment to impair chemotherapy response - Manoleras, Annabel V.; Sloan, Erica K.; Chang, Aeson (Frontiers in Oncology, 2024)
The tumor microenvironment influences cancer progression and response to treatments, which ultimately impacts the survival of patients with cancer. The sympathetic nervous system (SNS) is a core component of solid tumors that arise in the body. In addition to influencing cancer progression, a role for the SNS in the effectiveness of cancer treatments is beginning to emerge. This review explores evidence that the SNS impairs chemotherapy efficacy. We review findings of studies that evaluated the impact of neural ablation on chemotherapy outcomes and discuss plausible mechanisms for the impact of neural signaling on chemotherapy efficacy. We then discuss implications for clinical practice, including opportunities to block neural signaling to improve response to chemotherapy.